FEATURES OF THE COURSE OF PREGNANCY IN PREGNANT WOMEN WHO HAVE HAD COVID-19 (Western European Journal of Medicine and Medical Science, 2024)
COVID-19, caused by the SARS-CoV-2 virus, has significantly impacted healthcare systems worldwide, including maternal health. Pregnant women represent a vulnerable population due to physiological changes that increase susceptibility to infections and complications. This article examines the course of pregnancy in women who have recovered from COVID-19, highlighting its impact on maternal and fetal health, risks of adverse outcomes, and considerations for prenatal care. While most pregnancies proceed without severe complications, a history of COVID-19 may pose risks such as preterm labor, placental abnormalities, and altered immune responses. The study emphasizes the need for personalized care, continuous monitoring, and further research to better understand the interplay between pregnancy and post-COVID-19 conditions